Porous carbon derived from sorghum stalk for symmetric supercapacitors. Issue 105 (1st November 2016) - Ma, Guofu; Hua, Fengting; Sun, Kanjun; Zhang, Zhiguo; Feng, Enke; Peng, Hui; Lei, Ziqiang
Abstract : Sorghum stalk based porous carbons (SSCs) have been synthesized through a simple carbonization method at 800 °C used sorghum stalk as carbon precursor and ZnCl2 as activating agent. Abstract : Sorghum stalk based porous carbons (SSCs) have been synthesized through a simple carbonization method at 800 °C used sorghum stalk as carbon precursor and ZnCl2 as activating agent. The morphology and structure of the SSCs are investigated by scanning electron microscopy, transmission electron microscopy, nitrogen adsorption–desorption, Raman spectra and X-ray diffraction. Undergoes activation at optimal amount of zinc chloride (sorghum stalks to ZnCl2 is 1 : 1), the resulting samples, labeled as SSC1.0 has a porous texture with high specific surface area and efficient ion diffusion channels (1354.7 m 2 g −1 specific surface areas and 0.765 cm 3 g −1 pore volumes), and the sample also has superhydrophilicity characterized by water contact angles. As supercapacitor electrode, it can deliver 216.5 F g −1 specific capacitance at 0.5 A g −1, 75% capacitance retention even at 8 A g −1 in 2 mol L −1 KOH aqueous electrolyte and excellent cyclic stability with 92% capacitance retention after 5000 cycles at 5 A g −1 . Moreover, the assembled SSC1.0//SSC1.0 symmetric cell has wide voltage range of 1.8 V, and high energy density in 0.5 mol L −1 Na2 SO4 aqueous electrolyte.